Fire experiment on temperature distribution in an underground vertical car park. (November 2019) - Luo, Junli; Zhang, Xin; Zhao, Jiaming; Xu, Zhisheng
Abstract: The underground vertical car parks are usually highly closed with few entrances and exits, and moreover the compact parking of vehicles leads to dense combustible materials and great fire load. Therefore, it is of practical significance to investigate the temperature distribution of underground vertical car park. In this paper, temperature measurements were presented as obtained in an 1/5 scale-model experiment. Since the main objective of this paper was to investigate the impact of the heat release rate (HRR) and the smoke exhaust system on the temperature field in the underground car park fire. Different parameters were varied: the heat release rate (HRR) (the presence or not of the automatic sprinkler system); the smoke extraction system (on and off); the location of the measured point (above, opposite, or adjacent). The results showed that the heating effect of the car fire on the temperature of upper floors was greater than that of the opposite side floors; when the exhaust system turned on, the temperature of the floors above the fire would be increased, and the temperature of the floors opposite the fire changed inapparently.